Utility, promise, and limitations of liquid chromatography‐mass spectrometry‐based therapeutic drug monitoring in precision medicine By Vanessa P. Gaspar, Sahar Ibrahim, René P. Zahedi and Christoph H. Borchers. (25th November 2021) - Gaspar, Vanessa; Ibrahim, Sahar; Zahedi, René; Borchers, Christoph
Abstract : Drug pharmacodynamics is monitored by directly measuring physiological indices of therapeutic response. For many drugs, however, methods for the direct measurement of a drug's effect are either not available or not sufficiently sensitive. In these cases, the percentage of a drug, or its active moiety that actually reaches the systemic circulation and becomes available to its target, known as the drug bioavailability, has become the most accepted indicator of efficacy. This explains the importance of therapeutic drug monitoring (TDM), which is the analysis, assessment, and evaluation of the circulating concentrations of drugs in serum, plasma, or whole blood in order to ensure that the patient's drug concentrations are within the established therapeutic range for the respective indication. In this month's special feature, Christoph Borchers and co‐workers review the advances, challenges, and limitations of the existing repertoire of TDM methods, and discuss future opportunities for TDM‐based precision medicine. Dr. Borchers is Professor of Oncology in Faculty of Medicine at McGill University (Montreal Canada). His research involves the improvement, development, and application of proteomics and metabolomics technologies, especially quantitative techniques for clinical diagnostics.